Reconstructionism in Islamic Philosophy of Education: An Epistemological Analysis and Its Relevance to the Contemporary Age - Syarif, Nawa (Indonesian Journal of Multidisciplinary Educational Research, 2026)
This article analyzes reconstructionism in the philosophy of education and examines its integration within the perspective of Islamic epistemology. The study is motivated by the dominance of descriptive approaches in reconstructionist studies, which still rely heavily on rationality and empirical experience, thereby insufficiently accommodating the transcendental dimension. This research employs a qualitative approach based on library research, using philosophical-conceptual analysis through content analysis, hermeneutics, and conceptual analysis. The data sources include works of reconstructionist thinkers as well as modern Muslim scholars. The findings indicate that reconstructionism has the potential to serve as a transformative paradigm in education; however, it requires epistemological expansion. In the Islamic perspective, reconstruction has long been present through the concepts of ijtihad, tajdīd (renewal), and iṣlāḥ (reform), which integrate revelation, reason, and experience. Reconstruction in Islam is not solely oriented toward social change but also toward moral and spiritual transformation. This study concludes that the reconstruction of Islamic education can be formulated through the selection and reformulation of values grounded in the Qur’an and Sunnah, while remaining adaptive to modernity. Thus, reconstructionism from an Islamic perspective constitutes an integrative and contextual process of re-articulation.